ARSITEKTUR BIOKLIMATIK Usaha Arsitek Membantu Keseimbangan Alam dengan Unsur Buatan - Suwarno, Natalia; Ikaputra, Ikaputra (Universitas Atma Jaya Yogyakarta, 2020)
Earth is an ecological habitat for human and another living creature which consist of the natural environment and artificial environment. The Architect has shared a significant contribution to an environmental issue. Â Therefore, the new design concept of architecture and a new environment should consider in protecting the environment and try to minimize the effect of the environment as much as possible. Few ideas emerge in this situation, such as sustainable architecture, green building, ecological architecture, biophilic architecture, and bioclimate architecture. The aim of this article is trying to explain how the application of principal from bioclimatic architecture and the relation with the application to the chosen environment also fulfill user requirements and archive thermal comfort, visual comfort, acoustic comfort, and psychological comfort from its user.